Development of a contextual student worksheet on relations and functions to facilitate students' mathematical conceptual understanding - Dewi Yuliani; Atma Murni; Nahor Murani Hutapea (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
This research was motivated by the low ability of students to understand mathematical concepts. One of the efforts made to facilitate the ability to understand mathematical concepts is by developing Contextual Teaching and Learning LKPD. This research aims to produce valid and practical LKPD products to facilitate the ability to understand mathematical concepts. The form of this research is development research using the 4-D model (definition, design, development and distribution). The research subjects were class VIII of SMPN 32 Pekanbaru. Research instruments include interviews, observations, validation sheets, student response questionnaires. The data analysis technique is carried out by analyzing validation data and student response data. The results of data analysis showed that the LKPD developed had met valid standards with a percentage of 89.06% in the very valid category. The student response questionnaire met practical standards with a percentage of 89.62% in the very practical category. Based on the results of data analysis, it can be concluded that the LKPD developed meets the valid and practical criteria, so it can be used in the mathematics learning process.